STRATEGI PEMBELAJARAN BAGI ANAK BERKEBUTUHAN KHUSUS - Nuraini Nuraini (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Learning for children with special needs (students with special needs) requires a separate strategy according to their individual needs. The learning strategy is a learning procedure in assisting student learning efforts, organizing learning experiences, organizing and planning teaching materials, in order to create a more effective and efficient learning process to achieve learning goals. In order for the learning objectives to be achieved, it is necessary to choose the right learning strategy, for example, the teacher's mental retardation learning strategy can use cooperative learning strategies, behavior modification and individual strategies. Learning strategies for blind children can use expository, heuristic, and team learning strategies. Learning strategies for disabled people can be integrated, segressive and structuring the learning environment. Tunalaras can use biogenetic, behavioral, psychodynamic, and ecological learning strategies. The deaf can use deductive, inductive, heuristic, expository, classical, and behavior modification learning strategies.